Predictors of oral rotavirus vaccine immunogenicity in rural Zimbabwean infants. Issue 13 (17th March 2020) - Church, James A.; Chasekwa, Bernard; Rukobo, Sandra; Govha, Margaret; Lee, Benjamin; Carmolli, Marya P.; Ntozini, Robert; Mutasa, Kuda; McNeal, Monica M.; Majo, Florence D.; Tavengwa, Naume V.; Kirkpatrick, Beth D.; et al.
Abstract: Background: Oral rotavirus vaccines (RVV) have poor immunogenicity in low-income countries, for reasons that remain unclear. This study identified the determinants of RVV immunogenicity among infants in rural Zimbabwe. Methods: Anti-rotavirus IgA titres were measured among a sub-group of infants enrolled in the Sanitation Hygiene Infant Nutrition Efficacy (SHINE) trial (NCT01824940). SHINE was a cluster-randomized trial of improved infant and young child feeding, and improved water, sanitation and hygiene (WASH) in two rural Zimbabwean districts. Infants received RVV as part of the national immunisation programme. Among HIV-unexposed infants in the non-WASH trial arms, we evaluated associations between potential risk factors (vaccine schedule and dose, maternal and infant nutritional status, infant diarrhoea, and household environment) and RVV immunogenicity (seroconversion, seropositivity and geometric mean titres) using multivariable regression. Results: Among 219 infants with seroconversion data, 43 (20%) successfully seroconverted and 176 (80%) failed to seroconvert to RVV. Seroconversion was positively associated with a higher length-for-age Z-score (LAZ) around the time of vaccination (adjusted RR 1.27 (95% CI 1.04, 1.55), P = 0.021), and negatively associated with concurrent OPV and RVV administration (adjusted RR 0.36 (0.19, 0.71), P = 0.003). Among 472 infants with post-vaccination titres, a higher LAZ score was associated with increased seropositivity (aRR 1.21 (95% CI 1.06, 1.38), P = 0.004), and higher birthweight was associated with increased IgA titres (0.45 (95%CI 0.18, 1.09) U/mL greater per 100 g gain in birthweight; P = 0.001). Conclusions: Infant ponderal and linear growth were positively associated with RVV immunogenicity, while concurrent administration of OPV was negatively associated with RVV immunogenicity. Together, these findings suggest that improving foetal growth and separating RVV and OPV administration are plausible approaches to increasing RVV immunogenicity.